Pengaruh Modal Kerja dan Likuiditas terhadap Profitabilitas pada PT. Indofood Sukses Makmur Tbk yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2023 - Wau, Gloria; Sarjana, Samuel Horas (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research aims to determine the effect of working capital and liquidity on profitability at PT. Indofood Sukses Makmur Tbk is listed on the IDX. This research has independent variables working capital and liquidity, while the dependent variable is profitability. The data used is secondary data obtained from the official BEI website (www.idx.co.id). The population in this research is the financial statements of PT. Indofood Sukses Makmur Tbk for 2016-2023 and the sample used is the financial reports for quarter 1 to quarter 4, for the last 8 years, namely from 2016-2023. The data analysis method uses the T test and F test. The partial test results for working capital on profitability show a significant value of 0.910 > 0.05, the calculated t value is 0.114 < t table 2.045, it can be concluded that the results have no significant effect on profitability. The results of the partial liquidity test on profitability show a significant value of 0.993 > 0.05, the calculated t value is 0.008 < t table 2.045, it can be concluded that the results have no effect on profitability. Meanwhile, the results of the simultaneous test show that the F value is 16.726 > F table 3.328 and the significant value is 0.000 < 0.05, meaning that working capital and liquidity have an effect on profitability.